Optimum Operation Parameters of the Combination of a Mixed-Flow Dryer and Continuous in-Bin Aeration for Paddy under Malaysian Conditions - Intaravichai, Sakda (1994)
The design of a mechanical paddy dryer or any improvement of the dryer can be successfully done by incorporating all significant variables concerned in its operation through an optimization model. All constraints employed in the optimization model should satisfy local requirements and suitabilities. This study was conducted to determine the optimum parameters for the operation of a mixed-flow paddy dryer followed by continuous in-bin aeration. The aeration was provided to enhance the mixed-flow dryer operation. The optimization study was done by incorporating the working parameters of each operation in two separate empirical non-linear optimization models. The two models were associated in such a way that the optimum results of the mixed-flow drying were the inputs to the aeration stage, and vice versa. A computer simulation programme was used to obtain all pertinent information of each operation prior to developing the optimization model. A major modification was done to the mixed-flow drying simulation programme to make it suitable for simulating paddy drying under local conditions so that it can be used to evaluate the performance of an existing mixed-flow dryer. The simulated results of this programme agreed reasonably well with the actual tests conducted on the dryer. The optimum result showed that only two passes of the dryer operation and one period of the in-bin aeration were required for drying fresh wet paddy from moisture content of 30.50 to about 16.00 percent dry basis. Different optimum drying air temperature and airflow rate were obtained from each pass of the drying. The values of 70.48 degree Celsius and 10.00 kglm2.min were respectively the optimum drying air temperature and airflow rate of the first drying pass. For the second pass, the optimum drying air temperature of 77.05 degree Celsius and airflow rate of 5 kg/m2.min were obtained. An optimum aeration period of 32.31 hours with airflow rate of 0.77 m3/mt.min was required following the first drying pass. The grain germination of 94.71 percent and dry matter loss of 0.6 percent were the optimum grain quality criteria obtained from the study. An average specific energy requirement of 5.13 ML/kg of water removed at the net grain output capacity of 6.88 mt/hr were recorded for the optimum conditions.